Comparison of the Outcome of 35% Glycolic Acid and 30% Salicylic Acid Peels in Treatment of patients with Acne Vulgaris - Farwa Nasir Khan, Wajieha Saeed, Qurat-ul-Ain, Mahym Mansoor, Nuzha Niazi, Aqsa Imtiaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcome of 35% glycolic acid and 30% salicylic acid in patients with acne vulgaris. Study design: It was a randomized controlled trial. Plate and duration of study: Department of Dermatology at Mayo Hospital, Lahore from 31-08-2019 to 29-02-2020. Methodology: This study involved 120 patients of both genders with ages between 15 to 40 years, who presented with mild to moderate acne. These patients were randomly allocated into two treatment groups. Patients in Group-A were treated with 35.0% glycolic acid while those in Group-B with 30.0% salicylic acid. Outcome variable was mean of percentage reduction in acne severity index one month after treatment, which was noted and compared between the groups. A written informed consent was taken from each patient. Results: The mean age of the patients was 21.56±5.09 years. There was a female predominance with male to female ratio of 1:1.2. Majority (67.5%) of the patients had Fitz Patrick Type-V skin phototype while 39 (32.5%) patients had Type-IV phototype skin. The severity of acne was mild in 75 (62.5%) patients and moderate in 45 (37.5%) patients. There was no statistically significant difference in the mean acne severity index between patients treated with 30.0% salicylic acid versus 35.0% glycolic acid (16.52±3.69 vs.16.48±4.01 p 0.962) at baseline. Conclusion: Chemical peeling with 30.0% salicylic acid was found superior to 35.0% glycolic acid in patients with mild to moderate acne regardless of patients’ age, gender, BMI, skin phototype and severity of disease which advocates the preferred use of salicylic acid peeling in the management of patients with acne in future dermatologic practice.